High-resolution RHEED analysis of dynamics of low-temperature superstructure transitions in Ge/Si(001) epitaxial system - Dirko, Vladimir V.; Lozovoy, Kirill A.; Kokhanenko, Andrey P.; Voytsekhovskiy, Alexander V. (Nanotechnology)
In this paper, we analyze superstructural transitions during epitaxial growth of two-dimensional layers and the formation of quantum dots by the Stranski-Krastanov mechanism in elastically stressed systems by the reflection high-energy electron diffraction method. Detailed dependences of the periodicity parameter N of the 2 × N reconstruction on the effective thickness of the deposited material in a wide range of growth temperatures during epitaxy of germanium on a silicon surface with a crystallographic orientation (001) are obtained. Superstructural transitions and the change in the value of the parameter N at low temperatures of epitaxy in this system have been investigated for the first time. It is shown that the length of dimer rows in such a reconstruction during the growth of pure germanium on silicon can reach a value of no less than N = 11. A relationship is found between the value of the parameter N, determined by elastic strains in the system, and the critical thickness of the transition from two-dimensional to threedimensional growth. Based on this relationship, a physical mechanism is proposed that explains the nature of the temperature dependence of the critical thickness of the Stranski-Krastanov transition, which has been the subject of constant scientific disputes until now.